Experimental performance of refrigaration system using R134A-L203 nanorefrigerant - Mohamed Syahiriza Bin Mohamed Yusoff (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Nanofluids have been attractive for the last few year with the enormous potential to improve the efficiency of heat transfer fluids. The aim of the study is to conduct an experiment in order to compare the performance of refrigeration system by adding the surfactant into the nanofluid. The nanoparticles used in this experiment ware Al2O3 nanoparticles with the particles concentration 0.5 vol%. R134a (Molecular formular (CF3CH2F)) was chosen an the refigirant and surfactant that was used was PVP (polyvinylpyrrolidone), molecular formular (C6N9NO)n with the concentration of 0.5%. and 0.6%